Inclusion scolaire et précarisation des enseignantes en début de carrière : tensions entre idéaux pédagogiques et réalités du terrain - Bilodeau, Karine; Giguère, Émilie; St-Arnaud, Louise (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
This study examines the impacts of inclusive education on the experiences of early-career preschool and elementary school teachers in Quebec. Using a qualitative methodology involving individual interviews, photo elicitation, and group interviews with 25 teachers, the study highlights the challenges of managing heterogeneous classrooms and insufficient resources. Findings reveal a persistent perception of a divide between so-called “regular” students and those requiring “inclusion,” as well as tensions between organizational expectations and on-the-ground realities. These challenges intensify teachers’ feelings of powerlessness and professional precarity, while underscoring an urgent need for systemic support and tailored training. The study concludes that while the principle of inclusion is widely supported, it remains a source of emotional and professional strain due to institutional shortcomings. The findings would advocate for rethinking training frameworks and investing in adequate resources to ensure equitable and sustainable inclusion.